Eating Disorders, Body Dissatisfaction, and Health-promoting Lifestyle: Comparing Coeliac Patients with Healthy People : Eating Disorders, Body Dissatisfaction, and Health-promoting Lifestyle in Coeliac Patients - Bahrami , Faezeh; Farshbaf, Farnaz; Chodari, Leila (Archives of Advances in Biosciences, 2021)
Introduction: Celiac disease is associated with body, eating concerns, and life style problems. This study was performed with the purpose of comparing components of eating attitude, body dissatisfaction, and health promoting life style in celiac patients and with those in healthy people. Materials and methods: The method of the research is descriptive-causal comparative. The statistical population includes all 18-80 year-old celiac patients and healthy people from West Azerbaijan Province in 2016. Forty celiac patients were selected from those referred to the gastrointestinal clinic; 40 healthy people who were matched with respect to demographic characteristics were selected through availability sampling. They answered the Eating Attitude Test (EAT-26), the Body Image Concern Inventory (BICI), and the Health Promoting Life Style Profile (HPLP) questionnaires. Results: The results of multivariate analysis of variance showed that the means of eating attitude (F=27/64) and body image concern (F=10/48) in celiac patients are significantly higher than those in healthy people. Also, the mean of health promoting life style (F=18/89) in celiac patients is lower than that of healthy people. Conclusion: Eating disorder symptoms and body image concern in celiac patient are significantly more than those in healthy people; moreover, health promoting life style in celiac patient is more insufficient than that of healthy people. Therefore, it is essential to pay more attention to the psychological status of these patients.